The Impact of Disability on Intergenerational Care Needs of the Elderly in China. (May 2021) - Bai, Lan; Gu, Shuyan; Gu, Hai; Xu, Xinpeng; Nan, Cui; Li, Decheng; Di, Wu
This paper discussed the influence of disability and the degree of disability on the intergenerational needs of the elderly in terms of time and economy. The data is from the CLHLS in 2018. And the study discussed from 3 dimensions: nursing time, economic support, and medical cost support provided by children. The results showed that disability had a significant impact on the care time and medical expenses provided by adult children (care time: β = 45.631, P  < .001; medical expenses: β = 2017.664, P  < .01). Compared with the elderly with low degree of disability, the economic intergenerational care needs of the elderly with severe disability increased significantly (β = 2108.078, P  < .01). The results of sub sample regression show that the intergenerational care needs of the elderly in China are restricted by objective factors and have not been met. These findings revealed the current situation of intergenerational support for the disabled in China, and emphasized that the government should establish and improve the social formal care, gradually reduce the burden of care for children with disabled elderly families, and improve the quality of life of the disabled elderly.